Kerja Tahun di Tiga Binanga (Tinjauan Etnoarkeologi Transformasi Religi) - Defri Elias Simatupang (Balai Arkeologi Sumatera Utara, 2007)
AbstractKerja Tahun is a ceremonial give thanks to The God for has given a succesful yield. This is a product from past religion culture who still founded in every place, such as for Karonese in Tiga Binanga. There are many diffrences culture between now and the past that showing it have been transformated. This article want to compare it according to religion aspect.